Bilateral Renal Cortical Necrosis in Meningococcal Meningitis - C. Kennedy; S. Khilji; A. Dorman; J. Walshe (Case Reports in Nephrology)
Bacterial meningitis is a relatively common infection of the cerebrospinal fluid (CSF) and leptomeninges. The clinical picture evolves rapidly and, if treatment is delayed, can result in a variety of long-term sequelae, including death. Acute kidney injury in the setting of bacterial meningitis usually results from hypotension and volume depletion and resolves with appropriate treatment. Meningococcaemia with profound hypotension, and/or disseminated intravascular coagulopathy (DIC) may very rarely lead to bilateral renal cortical necrosis. In this context, renal recovery is extremely unlikely. We present two cases of meningococcaemia complicated by bilateral renal cortical necrosis and, ultimately, end stage kidney disease. We also present a review of the literature on the subject. The cases outline the importance of early aggressive intervention by a multidisciplinary team.